Large piezoelectric and thermal expansion coefficients with negative Poisson's ratio in strain-modulated tellurene. Issue 11 (27th April 2021) - Sachdeva, Parrydeep Kaur; Gupta, Shuchi; Bera, Chandan
Abstract : 2D tellurene monolayer exhibits excellent piezoelectric properties and an anomalous negative Poisson's ratio under the effect of strain. Tellurene having puckered structure has a large temperature dependent expansion. Abstract : Two dimensional (2D) chalcogenide monolayers have diversified applications in optoelectronics, piezotronics, sensors and energy harvesting. The group-IV tellurene monolayer is one such emerging material in the 2D family owing to its piezoelectric, thermoelectric and optoelectronic properties. In this paper, the mechanical and piezoelectric properties of 2D tellurene in centrosymmetric β and non-centrosymmetric β′ phases are investigated using density functional theory. β′-Te has shown a negative Poisson's ratio of −0.024 along the zigzag direction. Giant in-plane piezoelectric coefficients of −83.89 × 10 −10 C m −1 and −42.58 × 10 −10 C m −1 are observed for β′-Te under biaxial and uniaxial strains, respectively. The predicted values are remarkably higher, that is 23 and 12 times the piezoelectric coefficient of a MoS2 monolayer with biaxial and uniaxial strain in the zigzag direction, respectively. A large thermal expansion coefficient of tellurene is also estimated using quasi harmonic approximation. High piezoelectricity combined with exotic mechanical and thermal properties makes tellurene a very promising candidate in nanoelectronics.